A Case of Hepatic Portal Venous Gas: Hypothesis of a Transient Direct Communication between a Penetrating Antral Gastric Ulcer and Mesenteric Varices - Hassan M. Ghoz; Shamlan M. Sheikh; Kanika Khandelwal; Joseph Fiore; Nicholas James; Joel Weinstock (Case Reports in Gastrointestinal Medicine)
Hepatic portal venous gas (HPVG) is a rare radiological sign that usually signifies an acute intra-abdominal process, most commonly bowel ischemia and sepsis. Few reports described an association with underlying gastric pathologies. We report a 60-year-old patient who presented with melena and chills and was discovered to have a gastric ulcer that appeared to have penetrated into a mesenteric varix. This, in turn, likely caused development of HPVG associated with fungemia. Treatment with a proton pump inhibitor and bowel rest was sufficient to resolve symptoms and the HPVG.